PRODUCTION AND CHARACTERIZATION OF EXOPOLYGALACTURONASE FROM FUSARIUM OXYSPORUM F. SP. LYCOPERSICI. - D. NIRMALADEVI; M. ANILKUMAR; C. SRINIVAS (International Journal of Pharma and Bio Sciences, 2014)
Polygalacturonases (PGs) are pectinolytic enzymes with wide industrial applications. The demand for the enzyme and its producing organism is rapidly increasing. Enzymes from filamentous fungi have been subject to vast number of studies due to their functional role in the organism as well as their advantage as models for enzyme production and their characteristics. The objective of the study was to screen a large population of Fusarium oxysporum isolated from tomato fields of Karnataka, for PG production. The ability of the cultures to produce extracellular PG was investigated. The culture conditions providing high level of enzyme production were determined. A typical exoPG producing strain was identified. The exoPG exhibited maximal activity at pH 4.0, 50°C, 40 min and thermal and pH stability. Various metal ions tested showed a high inhibitory effect on PG activity. The Km and Vmax values were 7.69 mg/ml and 0.20 µmol/ml/min. The molecular weight of the enzyme was found to be 60 kDa.